“I’ve come too far, I’ve worked too hard”: Reinforcement of Support Structures Among Black Male Mathematics Students - Clarence L. Terry, Sr.; Ebony O. McGee (Journal of Mathematics Education at Teachers College, 2013)
Along with the growth and refinement of our shared discourses on equity, the community of education researchers focused on Black males has developed lenses with which to examine the risk and protective factors related to Black males’ participation in and experiences with mathematics. In this paper, the authors focus on the importance of the “supports” associated with mathematically high-achieving Black high school students in urban high schools. Using Critical Race Theory (CRT) and narrative analysis, the authors report findings from semi-structured interviews of mathematically successful Black male students (n = 12) from four urban high schools. Analysis of key themes suggests that high-achieving Black male mathematics students make use of powerful family & peer networks, as well as various features of the school and classroom community as support structures in the course of maintaining consistent mathematics achievement. Recommendations for strengthening support for all Black male mathematics students in urban contexts are discussed.